2015
DOI: 10.1017/thg.2015.42
|View full text |Cite
|
Sign up to set email alerts
|

A Common Genetic Influence on Human Intensity Ratings of Sugars and High-Potency Sweeteners

Abstract: The perception of sweetness varies among individuals but the sources of this variation are not fully understood. Here, in a sample of 1,901 adolescent and young adults (53.8% female; 243 MZ and 452 DZ twin pairs, 511 unpaired individuals; mean age 16.2 ± 2.8, range 12-26 years), we studied the variation in the perception of sweetness intensity of two monosaccharides and two high-potency sweeteners: glucose, fructose, neohesperidine dihydrochalcone (NHDC), and aspartame. Perceived intensity for all sweeteners d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…A recent study of 1,901 adolescent and young adult twins found that a common genetic factor accounted for 30% of the overall variance in their sensitivity to the sweet taste of two monosaccharides (glucose, fructose) and two nonnutritive sweeteners (neohesperidin dihydrochalcone, aspartame) [39]. While this twin study did not determine whether the common factor was the sweet taste receptor gene, other datareveal that (a) variation in the TAS1R3 subunit of the sweet taste receptor gene and (b) variation in the GNAT3 gene that encodes for the intracellular sweet transduction protein are related to sucrose detection thresholds (defined as the lowest concentration of a stimulus needed by a subject to detect its presence relative to water).…”
Section: The Biology Of Sweet Tastementioning
confidence: 99%
“…A recent study of 1,901 adolescent and young adult twins found that a common genetic factor accounted for 30% of the overall variance in their sensitivity to the sweet taste of two monosaccharides (glucose, fructose) and two nonnutritive sweeteners (neohesperidin dihydrochalcone, aspartame) [39]. While this twin study did not determine whether the common factor was the sweet taste receptor gene, other datareveal that (a) variation in the TAS1R3 subunit of the sweet taste receptor gene and (b) variation in the GNAT3 gene that encodes for the intracellular sweet transduction protein are related to sucrose detection thresholds (defined as the lowest concentration of a stimulus needed by a subject to detect its presence relative to water).…”
Section: The Biology Of Sweet Tastementioning
confidence: 99%
“…The mean intensity ratings from the duplicate presentations were used in this study. As our previous study showed that a common genetic component accounted for most of the variance in intensity scores of each sweetener (71% for glucose, 77% for fructose, 64% for NHDC, and 59% for aspartame; Hwang et al, 2015), here we calculated a general sweet intensity rating (gSweet) using the weighted mean of intensity ratings of the four sweeteners. Intensity scores were square-root transformed to approximate the normal distribution.…”
Section: Datamentioning
confidence: 99%
“…The 19Up study complements and extends earlier BLTS and BATS studies of mental health and well being in adolescence ( Figure 1) [51, [81][82][83][84][85][86][87][88][89] by providing a detailed assessment of mental health and substance use, and misuse from early teenage years through to young adulthood. The study was organised for the purpose of collecting lifetime diagnoses of substance misuse and common affective disorders, but also includes a range of behavioural and non clinical assessments, as well as updates on phenotypes previously collected in the BLTS (Figure 1).…”
Section: Introductionmentioning
confidence: 70%